Geochemical features of limestones in Arroyo Verde Formation (Eocene) in Punta Colorada, Río Negro Province, Argentina. Palaeoenvironmental reconstruction (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The fast growing cement industry has reactivated the exploration for calcareous materials in southern Argentina.A carbonatic deposit is found in Punta Colorada, located 36 km from the town of Sierra Grande, Río Negro Province. These rocks, deposited during a Late Cretaceous - Early Tertiary marine ingression, belong to Arroyo Verde Formation (Early Eocene).These coastal deposits have been studied since 1927 by Wichmann, Arnolds (1952), de Alba (1964), Weber (1983) and Busteros et al. (1998). Rossi de García and Levy (1982) assigned these rocks to the Eocene; Spalletti et al. (1993) located them within the Roca Formation (Rocanense ingression) and Gelós et al. (1992) correlated these rocks with Arroyo Verde Formation (Malvicini and Llambías, 1974).Arroqui Langer et al. (2006) from sedimentologic, geochemical and lithologic data in carbonatic rocks of the Precordillera Argentina established an exploration and exploitation pattern. Bonuccelli (2006) made a similar technical study in Punta Colorada, where 14,806,106 tn of measured reserves and 1,799,174 tn of indicated reserves were determined in a carbonate of less than 4% MgO grade.The study area comprises 800 Ha divided in two zones separated by Arroyo Las Palmas gully and located at the north and at the south of a basement outcrop denominated Punta Colorada, in the Atlantic marine coast (Fig. 1). By means of 12 drills cores and 8 stratigraphic profiles, a thickness of 10 m was determined for the limestone. Major and minor chemical elements were determined by ICP-MA in 100 ml with two replicas in Alex Steward laboratories, Mendoza. The criterion of Tucker (1981) was used to classify the limestones by the dolomite percentage.From stratigraphic profiles four levels composed of cross-bedded massive to granular fossiliferous limestones were determined. Microscopically they are composed of a fossiliferous limestone (bioclastic packstone) with bivalves, equinoderms, corals, foraminifera and algae, being algal buildups more abundant in level three. The clastic sand to silt fraction is mainly composed of quartz, feldspar and green clay concretions.CaO and MgO contents and the relationships Mg/ Ca (Tables 1 and 2) in the stratigraphic profiles and drills cores show vertical variations with increasing MgO values toward the upper levels of the sequence. Based on the percentages of these oxides the rocks are classified as limestone, dolomitic limestone and calcitic dolomite. In drill cores Al, Fe, K, Mg, Mn, Na, P, S and Ti contents, indicate lateral and vertical variations that would be related to geomorphological and paleoenvironmental changes and to the basin evolution as well (Fig. 2, Tables 1-3).It is concluded that the limestones are mainly composed of calcite with variable quantities of MgO. These rocks would have been formed in warm lagoons with high P content. At the same time shallower areas with intermittent influx of marine waters would have been developed in other sectors. The increase in the content of Na and K in these sectors would support the idea that these evaporitic deposits were temporarily isolated from the dominant marine environment. Al, Fe, Mn and Ti concentrations would be related to the presence of terrigenous material; however, the scarce contribution to the basin would indicate climatic conditions of aridity with low pluvial regimen. Crossbedding in level 2 is associated to marine currents.The abundance of broken fossils would indicate a highly energy environment. On the tidal flat, the presence of rather thin bioturbation traces (Thalassinoides) would indicate conditions of instability during the development of this ichnofacies, as well as a rather moderate energy with low sedimentation rates.At the final stage, shallow marine, coastal sedimentation prevail, marked by the abundance of entire shells, cross-bedding and an increment in the Fe and Mn concentration. At the same time in other sectors, the increase in the sulfur content as gypsum, would indicate a sustained SW-NE sea regression.
Keywords: Geochemistry; Limestones; Palaeoenvironment reconstruction; Arroyo Verde Formation; Eocene; Río Negro; Argentina.